1997
DOI: 10.1111/j.1365-2044.1997.091-az0086.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐breath inhalation induction of sevoflurane anaesthesia with and without nitrous oxide: a feasibility study in adults and comparison with an intravenous bolus of propofol

Abstract: SummaryThe induction characteristics of sevoflurane in nitrous oxide and oxygen were compared with sevoflurane in oxygen alone and a propofol infusion. A vital capacity technique was used for the gaseous induction groups using a Mapleson A system and a 4-litre reservoir bag. Four end-points of anaesthesia were recorded: time to cessation of finger tapping, time to loss of eyelash reflex, time to jaw relaxation and time to regular settled breathing after laryngeal mask airway insertion. We also recorded sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
83
5
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 11 publications
11
83
5
3
Order By: Relevance
“…Hall et al [6] in their study, found that sevoflurane was slightly slower for induction than propofol. In our study, we found that the induction time for sevoflurane was shorter than propofol.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hall et al [6] in their study, found that sevoflurane was slightly slower for induction than propofol. In our study, we found that the induction time for sevoflurane was shorter than propofol.…”
Section: Discussionmentioning
confidence: 89%
“…The conditions for LMA insertion after inhalation induction with sevoflurane are as good as with propofol [6]. However, inhalation induction with sevoflurane, without any co-induction agents produces more excitation before insertion of LMA and takes more time to produce jaw relaxation [6].…”
mentioning
confidence: 99%
“…Patients were instructed to take deep breaths at a normal rate and to tap their finger repeatedly on the edge of the trolley. Cessation of finger tapping was taken to signify loss of consciousness [8], which was confirmed by loss of the eyelash reflex. After loss of consciousness, ventilation was gently assisted by hand.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate this comparison, it would be necessary to administer the volatile agent for induction and maintenance of anaesthesia. Sevoflurane therefore appeared to be the most logical choice of volatile agent, as it has already been shown to be comparable with propofol during induction of anaesthesia [7,8], and it is increasingly used in day-case anaesthesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation